GW24-e3580 The atrial fibrillation registry in China: baseline characteristics and patient management. (1st October 2013) - Han, Zhang; Jun, Zhu; Yanmin, Yang
Abstract : Objectives: Atrial fibrillation (AF) is the most common arrhythmia; however, there is a paucity of data on Chinese AF patients. The objective of this study is to describe patient characteristics, risk factors, comorbidities, management strategy, and control of different types of AF in the emergency department (ED) daily practice. Methods: We conducted a prospective registry among 2016 participants presenting to an emergency department (ED) at 19 sites in China. AF cases were identified by the 12-lead body surface electrocardiogram. Patients demographics, medical history, type of AF, treatment, and outcome of emergency room visit were collected at baseline by the treating physicians using a standardised questionnaire. Results: Of the 2016 Chinese patients enrolled in this registry, the mean age was 68.5 ± 13.3 years, and 54.8% were women. 617 (30.6%) had paroxysmal, 449 (22.3%) had persistent, and 945 (46.9%) had permanent AF. The most common concomitant condition was hypertension, present in 1121 (55.6%) patients, followed by a history of coronary artery disease (41.8%), heart failure (37.3%) and current smoking (21.5%). In addition, rheumatic valve disease, diabetes mellitus, and history of stroke/transient ischaemic attack. History of stroke and transient ischaemic attacks were reported in 15.7%, 15.6% and 18.8% of patients, respectively. And some of these risk factors or comorbidities were present in patients with an increase as the AF progression.. The mean CHADS2 [cardiac failure, hypertension, age, diabetes, stroke (doubled)] score in patients with non-valvular atrial fibrillation (NVAF) was 1.9 ± 1.4, and 869 (53.8%) patients with CHADS2 ≥2 were qualified for oral anticoagulants (OACs), while only 109 (12.5%) did so, but 121 (15.9%) of those with CHADS2 <2 received anticoagulation therapy. And in 322 patients with valvular atrial fibrillation (VAF), 133 (41.4%) actually used OACs. However, INR value was measured in only 254 patients (69.6%), and within the target INR range (2.0–3.0) in 96 patients (26.3%). Almost one sixth of patients received ≥1 antiarrhythmic agents (AADs), while rate-control agents were used more frequently, especially in patients with permanent AF. Chemical cardioversion was performed over 30% of patients with paroxysmal and persistent AF. Conclusions: This registry provides insight into baseline characteristics and current primary medical care of patients with AF in China. The risk profile of Chinese patients was different from previous studies in other countries, and the use of oral anticoagulants was inadequately deviate from current guidelines.